Architects Play - Sebastián Trujillo-Torres (Architecture Image Studies Scientific Journal)
This paper deals with the gap that exists between two realities of practice: that which is idealized by architects, and that of its actual performative reality. The breach between preconceptions and circumstances that opens towards a spectrum of practice where architects play. A spectrum of practice where pragmatic yet imaginative roles are figured and lead towards playful dispositions, which are capable of subverting restrictions into advantages and outwitting stringent power structures.